Seasonal variations of cold hardiness and dormancy depth in five temperate woody plants in China - Hu, Zhi; Lin, Shaozhi; Wang, Huanjiong; Dai, Junhu (Frontiers in Forests and Global Change, 2022)
Woody plant species in temperate regions must withstand a cold winter and freezing events through cold acclimation and dormancy in autumn and winter. However, how seasonal changes in dormancy depth and cold hardiness affect the frost risk of temperate species is unclear because few studies have assessed dormancy depth and cold hardiness simultaneously. In this study, an experiment was conducted to estimate the dormancy depth and cold hardiness of five common woody temperate plant species during the winter of 2018/2019 in Beijing, China. Twigs of each species were collected at different dates during winter and the timing of budburst was monitored under the same forcing conditions. The dormancy depth was quantified as growing degree day (GDD) requirements of spring events. Simultaneously, the cold hardiness of buds at each sampling date was determined based on the electrical conductivity of the holding solution. Two indices (chilling accumulation and cold hardiness index) were used to simulate the past dynamics of dormancy depth, spring phenology, and cold hardiness from 1952 to 2021. The maximum dormancy depth of the study species was observed between early October and early December, and thereafter decreased exponentially. The cold hardiness peaked in mid-winter (end of December) through cold acclimation and thereafter decreased in spring (deacclimation). During the past 70 years, the budburst date (first flowering date or first leaf date) of five species was estimated to have advanced significantly, and dormancy depth in early spring was predicted to have increased owing to the warming-associated decrease in chilling accumulation. However, cold hardiness has decreased because of weakened acclimation and accelerated deacclimation under a warming climate. The frost risk before and after budburst remained unchanged because of the reduction in occurrence and severity of low-temperature events and earlier late spring frosts. The present methods could be generalized to estimate and predict the seasonal changes in dormancy depth and cold hardiness of temperate species in the context of climate change.